Neonatal meconium ileus: a rare presentation - Hemachandran, Sneha; J., Chaithanya; Kumar, Anjala; Murthy, Keshav; M. L., Girish (International Surgery Journal, 2019)
Meconium peritonitis is a non-bacterial, chemical inflammation of the peritoneum caused by antenatal or postnatal perforation of intestine by inspissated meconium. Surgery is necessary when signs of intestinal obstruction are present. The incidence of meconium peritonitis is about 1:30,000. Perinatal morbidity and mortality is about 80%. In the case of meconium peritonitis, the incidence of prematurity is 20-30 %. Author present an unusal case of meconium ileus with multiple ileal perforation leading to peritonitis.